Immune adjuvant therapy using Bacillus Calmette–Guérin cell wall skeleton (BCG-CWS) in advanced malignancies: A phase 1 study of safety and immunogenicity assessments. Issue 33 (August 2019) - Nishida, Sumiyuki; Tsuboi, Akihiro; Tanemura, Atsushi; Ito, Toshinori; Nakajima, Hiroko; Shirakata, Toshiaki; Morimoto, Soyoko; Fujiki, Fumihiro; Hosen, Naoki; Oji, Yusuke; Kumanogoh, Atsushi; Kawase, Ichiro; et al.
Abstract : Abstract: The cell wall skeleton of Bacillus Calmette–Guérin (BCG-CWS) is a bioactive component that is a strong immune adjuvant for cancer immunotherapy. BCG-CWS activates the innate immune system through various pattern recognition receptors and is expected to elicit antigen-specific cellular immune responses when co-administered with tumor antigens. To determine the recommended dose (RD) of BCG-CWS based on its safety profile, we conducted a phase I dose-escalation study of BCG-CWS in combination with WT1 peptide for patients with advanced cancer. The primary endpoint was the proportion of treatment-related adverse events (AEs) at each BCG-CWS dose. The secondary endpoints were immune responses and clinical effects. A BCG-CWS dose of 50, 100, or 200 μg/body was administered intradermally on days 0, 7, 21, and 42, followed by 2 mg of WT1 peptide on the next day. For the escalation of a dose level, 3 + 3 design was used. Study subjects were 18 patients with advanced WT1-expressing cancers refractory to standard anti-cancer therapies (7 melanoma, 5 colorectal, 4 hepatobiliary, 1 ovarian, and 1 lung). Dose-limiting toxicity occurred in the form of local skin reactions in 2 patients at a dose of 200 μg although no serious treatment-related systemic AEs were observed. Neutrophils and monocytes transiently increased in response to BCG-CWS. Some patients demonstrated the induction of the CD4 + T cell subset and its differentiation from the naïve to memory phenotype, resulting in a tumor response. The RD of BCG-CWS was determined to be 100 μg/body. This dose was well tolerated and showed promising clinical effects with the induction of an appropriate immune response. Abstract : Supplemental Digital Content is available in the text